DAMPAK MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP MOTIVASI BELAJAR PESERTA DIDIK SEKOLAH DASAR - irma susilawati; Yudi Bachtiar; Annisa Nurfitriani (STKIP Subang, 2026)
The learning motivation of fourth-grade students in Natural and Social Sciences (IPAS) remains relatively low, characterized by limited active participation, enthusiasm, and student engagement in the learning process. This condition highlights the need for implementing innovative learning models, one of which is Project Based Learning (PjBL). This study aimed to analyze the differences in learning motivation between students who learned using the Project Based Learning model and those who learned using conventional models, to measure the improvement in learning motivation through N-Gain analysis, and to examine the effect of Project Based Learning on the learning motivation of fourth-grade students in IPAS. This study employed a quantitative approach with a Quasi-Experimental Design in the form of a Nonequivalent Control Group Design. The sample consisted of two fourth-grade classes selected through purposive sampling, namely the experimental class and the control class. Data were collected using a Likert-scale learning motivation questionnaire and analyzed using normality tests, homogeneity tests, independent sample t-tests, paired sample t-tests, and N-Gain analysis. The findings revealed a significant difference in learning motivation between the experimental and control classes. The implementation of Project Based Learning had a significant effect on students' learning motivation. Although the improvement based on the N-Gain value was in the low category, all students in the experimental class achieved high and very high motivation categories.